Political Cohesion and Fiscal Systems in the Roman Republic - Tan, James (Frontiers in Political Science, 2022)
For over two centuries, the largest public revenue of the Roman Republic was a levy on property that was earmarked for infantry pay. It was collected by wealthy local landowners and redistributed to soldiers in the district. This article argues that the period of tributum was largely one of political calm because the tax systems effectively reinforced social and political hierarchies. Within three to four decades of tributum's invention, intra-elite politics began to stabilize, and within three to four decades of its cancellation, intra-elite politics began to destabilize. With little role for a central bureaucracy, local elites across the countryside used their roles as tax collectors to derive bargaining power in politics, but also to control local economies and to demonstrate their high rank in a society that revered public leadership in service of the military.